Changes in sleep Quality in Patients Older than 60 Years, Post-COVID Pandemic - Manuel R. Ramírez-Mexia; Yamile Martínez-Rodríguez; Mayomi Sierra-Lara; Andrea Espinosa-Arellano; Ivette Buendía-Roldán (Revista de Investigación Clínica)
Background: COVID-19 is a disease that had a great impact in the world, generating lifestyle changes; among these are changes in sleep quality, with the elderly being one of the most affected age groups. Objective: To identify sleep alterations in Mexican people older than 60 years post COVID-19 pandemic. Methods: We performed a descriptive study on subjects older than 60 years from the aging cohort of the National Institute of Respiratory Diseases. Demographic data, sleep questionnaires (Pittsburgh), and quality of life (SF-12) were assessed pre-pandemic. During the period from June 2021 to August 2022, the questionnaires were repeated post-pandemic through telephone. Qualitative variables were analyzed with frequencies and percentages, whereas quantitative variables were analyzed with means and standard deviations. The groups were compared using the X2 test and Student’s t-test. Results: We analyzed 279 subjects who completed two questionnaires. An alteration in sleep quality variables was observed post-COVID, including a decrease in sleep hours (7.33 h versus 7.17 h, p = 0.03), and a trend to a longer time to fall asleep (23 m vs 27 m, p = 0.06). In the questionnaire on toxicology, we found higher alcohol consumption (18% vs. 27%, p = 0.01) and vitamin ingestion (34% vs. 46%, p = 0.003). Subjects also described more nighttime awakenings, with more than 3 times per week (25% vs. 44%, p < 0.0001), generating a worse auto perception of healthy well-being (88.3 vs. 82.02 p < 0.0001). Conclusions: The COVID-19 pandemic affected sleep quality in different aspects, and it increased the consumption of alcohol and vitamins.